Yvain, the Knight of the Lion - Chrétien, de Troyes, active 12th century; Raffel, Burton (New Haven : Yale University Press, 1987)
The twelfth-century French poet Chrétien de Troyes is a major figure in European literature. His courtly romances fathered the Arthurian tradition and influenced countless other poets in England as well as on the continent. Yet because of the difficulty of capturing his swift-moving style in translation, English-speaking audiences are largely unfamiliar with the pleasures of reading his poems. Now, for the first time, an experienced translator of medieval verse who is himself a poet provides a translation of Chrétien's major poem, Yvain, in verse that fully and satisfyingly captures the movement, the sense, and the spirit of the Old French original. Yvain is a courtly romance with a moral tenor; it is ironic and sometimes bawdy; the poetry is crisp and vivid. In addition, the psychological and the socio-historical perceptions of the poem are of profound literary and historical importance, for it evokes the emotions and the values of a flourishing, vibrant medieval past.
Front matter -- Contents -- Translator's Preface -- Yvain: The Knight of the Lion -- Afterword -- Suggestions for Further Reading
Description based upon print version of record.
English
Includes bibliographical references.
Description based on online resource; title from PDF title page (ebrary, viewed October 12, 2013).
Keywords: Yvain (Legendary character) -- Romances; Arthurian romances; Romances -- Translations into English